Tracing the autobiographical - Kadar, Marlene, 1950- (Waterloo, Ont. : Wilfrid Laurier University Press, 2005)
Annotation Essays analyze the autobiographical impulse in variety of contexts, genres, and locations to reveal the intersections of personal revelation with vital modern and historical events.
Introduction: Tracing the autobiographical: unlikely documents, unexpected places / Jeanne Perreault, Marlene Kadar -- Katie.com: my story: memoir writing, the Internet, and embodied discursive agency / Helen M. Buss -- Reading the autobiographical in personal home pages / Linda Warley -- Reality TV has spoken: auto/biography matters / Gabriele Helms -- Performing the auto/biographical pact: towards a theory of identity in performance / Sherrill Grace -- Domestic space and the idea of home in auto/biographical practices / Kathy Mezei -- The shifting grounds of exile and home in Daphne Marlatt's Steveston / Susanna Egan -- Law stories as life stories: Jeanette Lavell, Yvonne Bédard, and Halfbreed / Cheryl Suzack -- Muriel Rukeyser: egodocuments and the ethics of propaganda / Jeanne Perreault -- Gender, nation, and self-narration: three generations of Dayan women in Palestine/Israel / Bina Toledo Freiwald -- Giving pain a place in the world: Aboriginal women's bodies in Australian stolen generations autobiographical narratives / Christine Crowe -- Circular journeys and glass bridges: the geography of postmemory / Adrienne Kertzer -- The devouring: traces of Roma in the Holocaust: no tattoo, sterilized body, gypsy girl / Marlene Kadar.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Autobiography; Autobiography in literature; Autobiographies as Topic; Autobiographie dans la littérature.; Autobiographie; autobiography (genre); TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Autobiography in literature; Autobiography; Autobiografie; Autobiografieën.